2015
DOI: 10.5296/ije.v7i2.7035
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Web-Cam Chat on the Undergraduate EFL Learners᾽ Socio-Cultural Competence

Abstract: This study aimed at investigating the use of web-cam chat as one of the most effective tools of Computer-Mediated Communication (CMC), and measuring its effect on the sociocultural competence of the English as foreign language learners. The sample of the study consisted of 38 undergraduate EFL learners who registered for a Conversational Skills Course at Al-alBayt University during the academic year 2013-2014. However, the chosen sample of the study was of two groups: Group one consisted of (20) students, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…The use of technology helped to develop students' communicative competence in the English language in general and in developing writing skill in particular. The results are consistent with previous studies (Al Abdali, 2016;Al-Abdali, 2017a and2017b;Al-Abdali, 2016, 2017a, 2017bAl-Temimi, 2017 andAbbas and Elttayef, 2019;Al-Abdali and Al-Temimi, 2018;Al-Abdali & Alzayadi, 2020;Al-Dulaimi & Al-Abdali, 2021;Bataineh & Al-Abdali, 2014;Bataineh & Al-Abdali, 2015;Elttayef, 2016;and Julaid and Al-Abdali, 2020, and 2022. These studies emphasize on the importance of using different types of technology in enhancing the level of English language learners.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The use of technology helped to develop students' communicative competence in the English language in general and in developing writing skill in particular. The results are consistent with previous studies (Al Abdali, 2016;Al-Abdali, 2017a and2017b;Al-Abdali, 2016, 2017a, 2017bAl-Temimi, 2017 andAbbas and Elttayef, 2019;Al-Abdali and Al-Temimi, 2018;Al-Abdali & Alzayadi, 2020;Al-Dulaimi & Al-Abdali, 2021;Bataineh & Al-Abdali, 2014;Bataineh & Al-Abdali, 2015;Elttayef, 2016;and Julaid and Al-Abdali, 2020, and 2022. These studies emphasize on the importance of using different types of technology in enhancing the level of English language learners.…”
Section: Discussionsupporting
confidence: 92%
“…Al-Abdali & Alzayadi (2020) and Al-Dulaimi & Al-Abdali (2021) explaine that this era is the era of technology, as it is not possible to imagine learning and teaching the English language without relying on modern technologies in teaching. Not far from other studies, Bataineh and Al-Abdali (2014), Bataineh and Al-Abdali (2015), and Elttayef (2016) conclude that the use of webcam chatting, as one of the elements of technology, is very effective for developing the linguistic competence as well as for developing the socio-…”
Section: Introductionmentioning
confidence: 91%
“…Different types of technology provide learners with a vast number of opportunities to develop their English which are not found in the traditional learning. Bataineh and Al-Abdali (2015) stated that "Technology has changed the teachers' and learners' roles, teaching changed from "teacher-centered into student-centered" (P. 243). This paper tries to show teaching and learning English language in the era of E-learning in Iraqi education.…”
mentioning
confidence: 99%
“…Regarding socio-cultural competence, a study that was conducted on 38 students who enrolled in the Conversational Skills Course at Al-alBayt University in Jordan revealed that webcam chat could enhance EFL learners' sociocultural competence. Besides, it was proved to be supportive of learning receptive and productive skills as well as improving learners' proficiency, fluency, accuracy, and mechanics of speaking and writing [21]. In fact, students also had positive interactions with their friends, their teachers, and their lesson in online classes [22].…”
Section: Literature Reviewmentioning
confidence: 97%